Dynamic and quasi-static modeling of planetary gear set considering carrier misalignment error and varying line of action along tooth width. (June 2015) - Cao, Zheng; Shao, Yimin; Zuo, Ming J; Liang, Xihui
Misalignment error of gear pair will affect the load distribution along the tooth-width and have a great effect on dynamic characteristics. For the planetary gear set, it is complicated to model the misalignment error of carrier as, when this error is present, the planets and the carrier are tilted and contacts between sun–planet and ring–planet along tooth width are skewed. In this paper, a new lumped parameter model is set up to quasi-statically and dynamic analyze the planetary gear set with the position-dependent line of action due to the misalignment of the carrier. In the analytical model, each potential line of contact on the gear mesh is discretized into finite independent time-varying stiffness. External and internal gear stiffness is obtained through the potential energy method. The dynamic responses, load distribution along the tooth width, load sharing between planets, trajectories of sun gear are simulated and analyzed with carrier misalignment error in planetary gear set.